2022
DOI: 10.1016/j.aninu.2021.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Responsive changes of rumen microbiome and metabolome in dairy cows with different susceptibility to subacute ruminal acidosis

Abstract: Subacute ruminal acidosis (SARA) represents one of the most important digestive disorders in intensive dairy farms, and dairy cows are individually different in the severity of SARA risk. The objectives of the current study were to investigate differences in the ruminal bacterial community and metabolome in dairy cattle with different susceptibility to SARA. In the present study, 12 cows were initially enrolled in the experiment. Based on average ruminal pH, 4 cows with the lowest ruminal pH were assigned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 53 publications
6
13
0
Order By: Relevance
“…Moreover, Prevotella is an essential microbial member that participates in the degradation of peptides into amino acids, which is regarded as the limiting process in proteolysis [56,57] and may explain the increase in growth performance (e.g., body weight gain) in our study. A high abundance of Prevotella rapidly and efficiently degrades soluble carbohydrates into glucose, and then, through the glycolysis pathway, it produces pyruvate, which is the main precursor for VFA production [58,59]. In the present study, the promoting effect of CS on Prevotella was consistent with the higher molar ratio of propionate, which presented a positive correlation between Prevotella and the production of propionate [60].…”
Section: Bacterial Diversity and Community In Response To Cs Additionsupporting
confidence: 81%
“…Moreover, Prevotella is an essential microbial member that participates in the degradation of peptides into amino acids, which is regarded as the limiting process in proteolysis [56,57] and may explain the increase in growth performance (e.g., body weight gain) in our study. A high abundance of Prevotella rapidly and efficiently degrades soluble carbohydrates into glucose, and then, through the glycolysis pathway, it produces pyruvate, which is the main precursor for VFA production [58,59]. In the present study, the promoting effect of CS on Prevotella was consistent with the higher molar ratio of propionate, which presented a positive correlation between Prevotella and the production of propionate [60].…”
Section: Bacterial Diversity and Community In Response To Cs Additionsupporting
confidence: 81%
“…Finally, purine degradation products are formed ( 60 ). Previous studies have demonstrated that high grain feeding increases rumen bacterial degradation products, such as xanthine and thymine ( 41 , 46 ). Among them, xanthine is considered a biomarker of microbial protein synthesis ( 10 , 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the activity of Prevotella spp. increased (p < 0.001); therefore, it seems that their activity increases when the population of cellulolytic bacteria in the ruminal fluid with a lower pH decreases since they are considered to be one of the main starch-degrading bacteria [28].…”
Section: Discussionmentioning
confidence: 98%